Human Embryonic Stem Cell Therapy in Chronic Spinal Cord Injury: A Retrospective Study. Issue 3 (3rd May 2016) - Shroff, G
Abstract : Human embryonic stem cells (hESCs) have a role in treating neurological disorders. The efficacy and safety of hESC in treating spinal cord injury (SCI) was reported in our previous study. In the present study, we have evaluated the efficacy and safety of hESC therapy in 226 patients with SCI. In the first treatment phase (T1), 0.25 mL hESCs were administered intramuscularly twice daily, 1 mL every 10 days i.v., and 1–5 mL every 7 days. Of 153 patients in the American Spinal Injury Association (ASIA) scale A at the beginning of T1, a significant number of patients ( n = 80; 52.3%) moved to lower scales at the end of T1 ( p = 0.01). At the end of T2, of 32 patients in ASIA scale A, 12 patients (37.5%) moved to scale B ( p = 0.01). Of 19 patients, 3 patients (37.5%) moved to scale B at the end of T3 ( p = 0.02). No serious adverse events (AEs) were observed. hESC transplantation is safe and effective.